2016
DOI: 10.1111/os.12240
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Pelvic Tumors Involving the Sacrum: Surgical Approaches and Procedures Based on a New Classification

Abstract: The proposed standardized protocols should help orthopaedic surgeons to achieve adequate margins, manage risk, achieve better oncologic and functional outcomes, and minimize perioperative complications when treating massive pelvic tumors involving the sacrum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Zhang et al 33 proposed a new classification of Enneking type 4 resections of the sacrum. They divided the excisions and reconstructive procedures into four subtypes (a to d) according to the extent of the tumour invasion in the sacrum.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al 33 proposed a new classification of Enneking type 4 resections of the sacrum. They divided the excisions and reconstructive procedures into four subtypes (a to d) according to the extent of the tumour invasion in the sacrum.…”
Section: Methodsmentioning
confidence: 99%
“…All sacral excisions will include lumbopelvic fixation with pedicle screw instrumentation. 33 When the excision also includes the acetabulum, the lumbopelvic instrumentation can be connected into a modular hemipelvic prosthesis. 6 , 9 , 16 …”
Section: Methodsmentioning
confidence: 99%
“…Due to the deep location of primary bone tumors abutting the sacroiliac joint, the tumors may invade the sacroiliac joint or even cross it at the time of diagnosis. Preoperative accurate diagnosis of transarticular invasion of the sacral or iliac tumor plays an important role in the design of surgical program [1][2][3][4] . [2] For primary malignant bone tumors involving the sacroiliac joint, it is necessary to resect the ilium and sacrum invaded by the tumors together with the sacroiliac joint and to reach the safe boundary of oncology [1] .…”
Section: Introductionmentioning
confidence: 99%
“…[2] For primary malignant bone tumors involving the sacroiliac joint, it is necessary to resect the ilium and sacrum invaded by the tumors together with the sacroiliac joint and to reach the safe boundary of oncology [1] . The postsurgical recurrence rate of tumors in patients reaching the safe boundary was much lesser than that in patients not reaching the safe boundary [3][4][5] . Imaging studies of pelvic bone tumors invading the sacroiliac joint have been rarely reported in the literature [2,[6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…Abdominal aortic balloon occlusion has been successfully implemented in controlling bleeding in sacropelvic resections [10,14,15,26,33]. Because most sacral tumors receive a blood supply from the iliolumbar arteries and the lateral sacral arteries originating from the internal iliac artery, by placing the aortic balloon cephalad to the iliac bifurcation and inflating it to an expected pressure, blood flow to the sacral tumor can be minimized [29].…”
Section: Introductionmentioning
confidence: 99%